Annual plant reviews, Volume 44: Oceanography and Marine - Gibson, R. (CRC Press, 2009)
# Presents authoritative and carefully edited reviews on various selected topics in the field of marine biology # Includes comprehensive reference list # Provides in-depth coverage of a variety of topics in numerous disciplines # Features a full color insert